Expression of Opioid Receptors in Cells of the Immune System - Brejchova, Jana; Holan, Vladimir; Svoboda, Petr (International journal of molecular sciences, 2020)
The observation of the immunomodulatory effects of opioid drugs opened the discussion about possible mechanisms of action and led researchers to consider the presence of opioid receptors (OR) in cells of the immune system. To date, numerous studies analyzing the expression of OR subtypes in animal and human immune cells have been performed. Some of them confirmed the expression of OR at both the mRNA and protein level, while others did not detect the receptor mRNA either. Although this topic remains controversial, further studies are constantly being published. The most recent articles suggested that the expression level of OR in human peripheral blood lymphocytes could help to evaluate the success of methadone maintenance therapy in former opioid addicts, or could serve as a biomarker for chronic pain diagnosis. However, the applicability of these findings to clinical practice needs to be verified by further investigations.
Keywords: Inflammation; Gene Expression Regulation; zánět; Analgesics, Opioid; opioidní analgetika; imunitní systém; regulace genové exprese; Receptors, Opioid; zvířata; Humans; addiction; biologické markery; opioid receptors; immune cells; chronic pain; Immune System; Stem Cells; receptory opiátové; opioid drugs; kmenové buňky; Biomarkers; Chronic Pain; lidé; stem cells; chronická bolest; Animals